Development of a series of novel o-phenylenediamine-based indoleamine 2, 3-dioxygenase 1 (IDO1) inhibitors. Issue 4 (15th February 2018) - Williams, David K.; Markwalder, Jay A.; Balog, Aaron J.; Chen, Bin; Chen, Libing; Donnell, Jennifer; Haque, Lauren; Hart, Amy C.; Mandal, Sunil K.; Nation, Andrew; Shan, Weifang; Vite, Gregory D.; et al.
Graphical abstract: A novel series of o -phenylenediamine-based inhibitors of indoleamine 2, 3-dioxygenase (IDO) has been identified. Compound 19 demonstrated significant potency in the HeLa human cervical cancer IDO1 assay. Abstract: A novel series of o -phenylenediamine-based inhibitors of indoleamine 2, 3-dioxygenase (IDO) has been identified. IDO is a heme-containing enzyme, overexpressed in the tumor microenvironment of many cancers, which can contribute to the suppression of the host immune system. Synthetic modifications to a previously described diarylether series resulted in an additional degree of molecular diversity which was exploited to afford compounds that demonstrated significant potency in the HeLa human cervical cancer IDO1 assay. .